Non-mosaic partial duplication 12p in a patient with dysmorphic characteristics and developmental delay - Oliveira,Jakeline Santos (2020)
Abstract Duplication of the short arm of chromosome 12 is a rare chromosomal abnormality that may arise de novo or result from malsegregation of a balanced parental translocation. This study comprises the clinical description, cytogenetic and cytogenomic analyses and genotype-phenotype correlation in a patient with facial dysmorphism, developmental delay and intellectual impairment caused by non-mosaic partial duplication and a paracentric inversion 12p. The patient’s GTG-banded karyotype was 46,XX,invdup(12)(pter → p13.32::p11.1 → p13.31::p13.31 → qter). A genetic gain of approximately 28 Mb was detected in the chromosomal region arr[GRCh37]12p13.31-p11.1(6914072_34756209)x3. The chromosomal alteration seen in our patient is described as “pure” partial duplication 12p. In most cases, duplication 12p phenotype is characterized by dysmorphic features, multiple congenital anomalies and intellectual disability. A small number of cases in literature have described genes associated with neurodevelopmental disease, such as ING4, CHD4, MFAP5, GRIN2B, SOX5, SCN8A and PIANP. In our patient the duplication 12p was de novo. This study should contribute to the genotype-phenotype correlation in partial duplication 12p cases.